Reflections on my Foray into the Battle of Open Access - Calomino, Brianna (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
The movement towards Open Access is an important one, yet it is fraught with challenges surrounding misinformation, a lack of awareness, and a lack of institutionally-supported motivational initiatives. One new Library and Information Science Professional reflects on what it was like to support Open Access in her first job in an academic library, and her struggles and experience with wanting to implement more change than was realistically possible. This article also describes an example of running an Open Access Escape Room as an Open Access initiative, and explores the benefits of the gamification of learning. Not letting go of the goal of information accessibility for all, this young professional finds value in the small wins working towards large-scale positive change.